[PP.01.30] THE HYPERTENSIVE POPULATION IN THE INTERNAL MEDICINE WARD. (September 2017) - Rodrigues, J.; Ferreira Simões, A.; Freixa, M.; Úria, S.; Silva, G.
Abstract : Objective: The global burden of arterial hypertension (AH) is substantial, with a prevalence of 42, 2% in Portugal, therefore constituting a major health concern. The authors intended to characterize the patients hospitalized with diagnosis of AH and identify differences when compared to those without this diagnosis. Design and method: Observational retrospective study based on the collection of clinical data of patients admitted in an internal medicine ward during 60 months. The patients were divided in two groups: those with the diagnosis of AH prior to or established during the hospitalization; and those without this diagnosis (NAH) at the time of hospital discharge. The sample was also divided by age tertiles: < 75 years; 76–83 years; > 83). There was defined as cardiovascular event the occurrence of stroke or acute myocardial infarction as motif or during hospitalization and was registered all cause death. Results: Total sample includes 1106 patients, from which 68.5% (n = 758) have the diagnosis of AH (n = 758). (1) In the AH group the female gender is more frequent (53.3% vs 50% in NAH group; p = 0.331) and the mean age is superior (79 ± 11.1 vs 72 ± 18.3 years; p < 0.001). (2) The prevalence of AH is higher as the population gets older (59.7%; 71.3%; 75.1%; p < 0.001). (3) The length of stay is slightly greater in the AH group (10.3 ± 9.4 vs 10.1 ± 10.4 days; p = 0.696). (4) The risk of AH is greater in the patients with diabetes mellitus (OR 2.7; 95% CI: 2–3.7; p < 0.001), dyslipidemia (OR 2.6; 95% CI: 2–3.6; p < 0.001), obesity (OR 3.0; 95% CI: 1.6–5.5; p < 0.001) and kidney failure (OR 2.3; 95% CI: 1.7–3.1; p < 0.001). (5) Most of the patients with cardiovascular events (73.2%; p = 0.555) or death in the hospital (51.8%; p = 0.008) have the diagnosis of AH. Conclusions: AH is a very common diagnosis in the patients admitted to the Internal Medicine ward, particularly in the older ones, and represents a risk factor to other cardiovascular diseases and mortality. For this reason, the authors intend to draw attention to the need of establishing prevention strategies, earlier detection and adequate treatment, in order to prevent other cardiovascular diseases and mortality.